The Importance of Consumer Protection in the Insurance Sector in Indonesia - Jeki Saroha Tamba; Martono Anggusti; Ria Juliana Siregar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Consumer protection plays a crucial role in the insurance industry due to the complex, long-term, and trust-based nature of insurance products. Consumers are often in a vulnerable position because of limited access to information and a lack of understanding of policy terms, which increases the risk of losses, especially during claim settlement processes. This study aims to analyze the factors that influence the importance of consumer protection in Indonesia’s insurance sector and to examine the role of the Financial Services Authority (OJK) as the regulatory and supervisory body in financial services. The findings indicate that low financial literacy, information asymmetry, and the dominance of standard contracts are key factors that underscore the need for consumer protection. Meanwhile, OJK plays a strategic role through regulation, supervision, dispute resolution, and financial education for consumers. This study concludes that the effectiveness of consumer protection in the insurance sector depends largely on the synergy between strong regulations, consistent supervision, and improved public awareness of consumer rights.